Application of GPS and GIS to study foraging behavior of dairy cattle - Mora-Delgado, Jairo (2016)
The use of Global Positioning Systems (GPS) to discriminate foraging activities of dairy cattle was evaluated at the robotic and pasturebased dairy farm of the WK Kellogg Biological Station, Michigan State University, during August 11-20, 2010. Visual scans of foraging activities and recording of locations and activity sensors were conducted on 4 lactating Holstein dairy cows (650 kg LW; 23 kg.day-1) equipped with GPS collars that register head position, X-axis and Y-axis movement sensors. Results from GPS collars showed 82-86% probability of estimating animal locations with a 7 m error. GPS data suggested cows were on pasture most of the time 94.6% (±0.92) and under barn only 5.4% (±0.92). When cows were on pasture, they spent most of the time grazing (51%); the remaining time was devoted to resting (43%) and traveling (6%); cattle traveled an average 3385 m±712 SE per day. In low-temperature days the main activity of cows was grazing (92%), but under medium and high temperatures grazing was only 62.6 and 59.4%, respectively. On the contrary, resting was most important under medium and high temperaturas (33.6 and 31.8%, respectively). The usefulness of remote sensing and GPS to monitor animal behavior was demonstrated.